2020
DOI: 10.3390/geriatrics5040076
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Male Hypogonadism and Cognitive Impairment in the Elderly: Focus on the Effects of Testosterone Replacement Therapy on Cognition

Abstract: Background. Epidemiological data report that male hypogonadism may play a role in cognitive impairment in elderly. However, the effect of testosterone replacement therapy (TRT) on cognitive abilities in this cluster of patients has not been well established. Methods. PubMed/MEDLINE, Google Scholar, Cochrane Library, and Web of Science were searched by using free text words and medical subject headings terms related with “male hypogonadism”, “late-onset hypogonadism”, elderly, cognition, “mild cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 97 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Some clinical data also show that there is serious cognitive impairment in senile CHF itself, and diabetes is the main factor in the development of CHF, and type 2 diabetes mellitus (T2DM) is especially common in CHF patients with CI [11][12][13]. e mortality caused by the combination of the two is higher than that in nondiabetic patients, which further aggravates the cognitive impairment, increases the hospitalization rate and mortality, and the quality of life of patients is seriously affected [14,15]. However, some studies have found that type 2 diabetes is the main factor leading to dementia and cognitive impairment in patients with CHF, and type 2 diabetes is likely to be an independent risk factor for CI [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical data also show that there is serious cognitive impairment in senile CHF itself, and diabetes is the main factor in the development of CHF, and type 2 diabetes mellitus (T2DM) is especially common in CHF patients with CI [11][12][13]. e mortality caused by the combination of the two is higher than that in nondiabetic patients, which further aggravates the cognitive impairment, increases the hospitalization rate and mortality, and the quality of life of patients is seriously affected [14,15]. However, some studies have found that type 2 diabetes is the main factor leading to dementia and cognitive impairment in patients with CHF, and type 2 diabetes is likely to be an independent risk factor for CI [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with those of a recent meta-analysis [ 11 ]. We speculated that the main reasons for this are as follows: First, aging is associated with a decline in anabolic hormone levels, such as testosterone [ 45 ], and growth hormone [ 46 ], which play crucial roles in muscle protein synthesis and maintenance. Consequently, older adults may excessively rely on alternative pathways for muscle protein synthesis, with BCAAs as important substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, testosterone replacement therapy (TRT) can be a tool that aids in health restoration since low endogenous levels (<300 ng/dL) of this hormone might result in health complications (Jia et al, 2015; Shin & Park, 2019). Although, for replacement therapy to be administered, an individual must be diagnosed with hypogonadism, which appears primarily associated with age (Kaufman & Vermeulen, 2005; Lisco et al, 2020; Wu et al, 2008). The benefits of TRT, when natural production is low, will improve a myriad of health markers, such as bone density, sexual function, depression and muscle mass, and it may also help prevent cardiovascular disease and metabolic syndrome (Bassil et al, 2009; Bhasin, 2021).…”
Section: Health and Testosteronementioning
confidence: 99%